ANALYSIS OF THE EFFECT OF INDIRECT COSTS ON THE PERFORMANCE OF CONSTRUCTION PROJECT IMPLEMENTATION - Ihsan (LPPM Universitas Negeri Jakarta, 2023)
The phenomenon that is currently happening in the field, especially in the implementation of the construction of flats within the work unit of the Ministry of Public Works and Public Housing, contractors who provide offers with an indirect cost of ≤ 10% on average there is a change in the time for completion of work implementation, while there are several implementing contractors who do not offer indirect costs but can complete the job on time. The purpose of this research is to find out whether indirect costs affect the performance of construction project execution time. The type of research used is a mixed method, namely quantitative methods and qualitative methods, in which data collection is carried out based on relevant theories and data sourced from the apartment development project within the work unit of the Ministry of Public Works and Public Housing. Data processing was carried out by distributing questionnaires to respondents and analyzed using statistical analysis methods with the help of Microsoft Excel and SPSS version 24 software. The results of the analysis show that the granting of indirect costs in the project budget plan has a significant effect on the performance of construction project implementation time taking into account the influence of (1) environmental factors, (2) claims policy factors and government regulations, (3) organizational factors and (4) project factors